Hepatitis C virus replication - Tabata, Keisuke; Neufeldt, Christopher; Bartenschlager, Ralf (Cold Spring Harbor perspectives in medicine, 2020)
Replication and amplification of the viral genome is a key process for all viruses. For hepatitis C virus (HCV), a positive-strand RNA virus, amplification of the viral genome requires the synthesis of a negative-sense RNA template, which is in turn used for the production of new genomic RNA. This process is governed by numerous proteins, both host and viral, as well as distinct lipids and specific RNA elements within the positive- and negative-strand RNAs. Moreover, this process requires specific changes to host cell ultrastructure to create micro-environments conducive to viral replication. This review will focus on describing the processes and factors involved in facilitating or regulating HCV genome replication.